Rice Fields Suitability Zonation in North Penajam Paser Regency Using Multicriteria-Based Simple Additive Weighting (SAW) and GIS - Fitriana, Lely; Susanto, Sahid; Supadmo, Sigit; Ngadisih, Ngadisih; Setyawan, Chandra; Zaki, Khoiru (Indonesian Journal of Geography, 2025)
The East Kalimantan Provincial Government has designated North Penajam Paser Regency as one of rice food supports for the National Capital City (IKN) of the Archipelago. This decision is based the domestic production which met and even exceeded demand in 2020. One step to support rice production is to identify land with the greatest potential for cultivation. Therefore, this study aimed to analyze land suitability zonation for rice production using the criteria of climate, topography, and soil properties, as well as infrastructure. Land suitability was evaluated using simple additive weighting (SAW), multicriteria, and GIS methods taking into account the factors of drainage, soil depth, texture, type, rainfall, temperature, slope, distance from road, distance from river, and land use land cover. Suitability zonation (classes) were arranged based on land suitability classification outlined by the Food and Agriculture Organization (FAO, 1976) in Minister of Agriculture Regulation No. 79 of 2013, namely Very Suitable (S1), Moderately Suitable (S2), Marginally Suitable (S3), Not Suitable (N1). The results showed that the areas classified as highly, moderately, marginally, and not suitable were 4,960 ha (3.1%), 103,738 ha (65.5%), 44,889 ha (28.4%), and 4,708 ha (3.0 %) respectively.Received:2024-02-01 Revised:2024-09-26 Accepted:2025-03-11 Published: 2025-04-27